Review of Static Transfer Switch Applications in AC Power Systems: Enhancing Reliability and Fault Tolerance - Sithole, Tshepo; Veerdhi, Vasudeva Rao; Sithebe, Thembelani (International Journal of Electrical, Energy and Power System Engineering, 2025)
This paper presents a comprehensive review of static transfer switch (STS) applications in AC power systems, with a focus on enhancing reliability and fault tolerance. The review outlines the fundamental requirements for effective STS deployment, including the necessity of two truly independent and nominally synchronized AC power sources, optimal placement of the STS near protected loads, and proper grounding practices to minimize single points of failure. The analysis synthesizes recent literature on STS topologies, control mechanisms, and integration with uninterruptible power supplies (UPS), highlighting the importance of redundancy and the persistent challenges of achieving source independence and synchronization. Empirical studies and case analyses are discussed to demonstrate the impact of STS design and deployment on minimizing risks to sensitive loads. The paper concludes by providing practical recommendations and identifying future research directions for further improving STS solutions in resilient AC power systems.